Hyaluronic acid as an active agent to accelerate bone regeneration aftertooth extraction: a literature review - I Putu Gede, Andyka Yasa; I Made Jawi; I Made Muliarta (Indonesian Journal of Pharmacology and Therapy, 2020)
Tooth extraction is a dental treatment that is performed frequently in dentistry. This procedure will stimulate a sophisticated healing process involving a variety of biological factors although it takes a long time to complete. Three phases occur in this process i.e. the inflammatory phase, the proliferation phase, and the remodeling phase which aim to restore the tissue function. Several interventions can be used to accelerate bone formation after tooth extraction. Recently, hyaluronic acid (HA) has been commonly used in dentistry due to their essential physiological effects for the periodontal connective tissue, gingiva, and alveolar bone. Hyaluronic acidis a natural non-sulfate glycosaminoglycans compound that has high molecular weight consisting of D-glucuronic acid and N-acetylglucosamine. Hyaluronic acidis also a component of the extracellular matrix that plays an important role in morphogenesis and tissue healing. The mechanism of action of HA works in two ways, that is passive and active mechanism. The passive mechanism is depend on physical and chemical properties of HA that can change the molecular weight and concentration properties. The active mechanism of HA works by stimulating signal transduction pathway initiated by ligand binding with its receptors through autocrine or paracrine processes. The administration of HA can accelerate bone formation due to it can enhance bone morphogenetic protein (BMP) which belongs to the TGF- β superfamily that has high osteogenic capacity. The HA works through a passive mechanism that depends on its molecular weight and an active mechanism by increasing BMP activity.